Evaluating electrostatic spraying to improve food contact surface decontamination and produce safety and quality - Kwamikorkor, Comfort Kafui Afra (My University, 2025)
The demand for fresh produce highlights the need to maintain its safety, quality, and availability throughout the year. However, there has been an increase in foodborne outbreaks related to fresh produce due to microbial contamination. Escherichia coli O157, Salmonella spp., and Listeria monocytogenes are particularly known bacteria associated with multistate outbreaks, making them pathogens of concern. Bacterial contamination can occur at any stage of the food supply chain, from pre-harvest to post-harvest. Animals, soil, workers, and agricultural water can compromise the safety of fresh produce. This review provides an overview of the safety risks of fresh produce from the three common pathogens: Listeria monocytogenes, Salmonella spp., and Escherichia coli O157:H7. It also discusses cross-contamination from food contact surfaces to produce, sanitation practices in the fresh produce industry, electrostatic spraying as an alternative solution for surface decontamination, and future studies on its application. The primary goal of this chapter is to review sanitation practices in the fresh produce industry and to evaluate electrostatic spraying technology as an emerging solution for food contact surface decontamination, enhancing fresh produce safety and quality.
Keywords: Postharvest sanitation practices; Electrostatic sprayer; Fresh produce; Fresh produce safety; Fresh produce quality; Listeria